Penerapan Model Pembelajaran Stad (Student Team Achivement Divisions) dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Ekonomi Kelas X SMA Negeri 1 Tanjung Morawa - Amini Amini; Feny Rosanti; Haikal Dipo Nugraha; Saskia De Vanny; Siti Maimunah; Winda Sapitri (Departement of Mathematics Education, 2023)
The learning that is carried out should be fun for students so that it can increase student learning motivation so that it helps improve student learning outcomes. In fact, some teachers prefer to apply conventional learning models. The STAD type cooperative learning model is one of the solutions to overcome this. STAD (Student Team Achievement Division) is the simplest cooperative learning, and is a suitable cooperative learning used to activate students. The result of the application of STAD carried out by the teacher is that STAD can improve learning outcomes for students.The purpose of learning is to achieve the target of mastering the material conveyed by the teacher to students and indicators of achieving this target are student learning outcomes will be good and increase if active interaction occurs in the learning process between the teacher and students. The interaction will arise if there is a feedback from students and good learning must arise from the wishes of the students themselves. This happens when students are happy and do not feel bored with the lesson being delivered.